Relationships between the allozyme and phenotypic diversities of Picea ajanensis populations - V. P. Vetrova; A. K. Ekart; A. N. Kravchenko; A. Ya. Larionova (Вавиловский журнал генетики и селекции)
The structures of Picea ajanensis populations were compared based on allozyme analysis of vegetative buds and morphometric analysis of generative organs. Six cenopopulations of P. ajanensis were investigated in areas with various levels of volcanic impact in the Kamchatka Peninsula. The genetic structures of spruce populations and phenotypes were determined by analysis of ten enzyme systems (PGM, GOT, HK, LAP, MDH, SKDH, IDH, GDH, PGI and SOD). Phenotypic variability of spruce populations was estimated based on the composition of morphotypes that were identified by using geometric morphometrics of cone-scale shapes. Pairwise comparison of samples of cones from 170 trees from six populations revealed 12 morphotypes differing in the shape of cone scales. Comparative assessment of variability and similarity of populations was carried out based on the frequency of occurrence of phenotypes and frequency of alleles of polymorphic loci. Correlations of the genetic and phenotypic distance matrices between different phenotypes were revealed. This observation was consistent with the genetic determination of the shape of cone scales in spruce. Genetic differences between the morphotypes with regard to nine polymorphic loci (Got-2, Skdh-1, Idh-2, Pgm-2, Mdh-1, Mdh-3, Pgm- 1, Pgi-2, and Hk) were not significant. Statistically significant differences between the morphotypes were revealed for two loci: Pgm-2 and Mdh-1. Differences in the genetic diversity of spruce populations generally corresponded to differences in their phenotypic diversity. The high levels of genetic and phenotypic diversity characterized a stable population structure of spruce in the area of weak volcanic influence. Changes in the genetic structure and low levels of the phenotypic diversity of spruce were observed under catastrophic volcanic impact.